2017
DOI: 10.1063/1.4985626
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mobility of water confined in AlPO4-54 nanotubes

Abstract: We performed molecular dynamics simulations of water confined within AlPO-54 nanotubes. AlPO-54 is an artificial material made of AlO and of PO in tetrahedra arranged in a periodic structure forming pores of approximately 1.3 nm in diameter. This makes AlPO-54 an excellent candidate for practical applications, such as for water filtration and desalination. In this work, the structural and dynamical properties of the confined water are analyzed for various temperatures and water loadings. We find that the water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 49 publications
0
17
1
Order By: Relevance
“…Data are also available for theoretical confining media and some less frequently used materials, which are summarized in this section. Other confining materials with available selfdiffusion coefficient data are ionomers (Berrod et al, [260]), aluminum phosphate nanotubes (Gavazzoni et al, [261]), polyamide RO membranes (Ding et al, [262]), boron nitride nanotubes (Won and Aluru [263]), and surfactants such as Newton Black films (Di Napoli and Gamba, [264]).…”
Section: Other Confining Mediamentioning
confidence: 99%
“…Data are also available for theoretical confining media and some less frequently used materials, which are summarized in this section. Other confining materials with available selfdiffusion coefficient data are ionomers (Berrod et al, [260]), aluminum phosphate nanotubes (Gavazzoni et al, [261]), polyamide RO membranes (Ding et al, [262]), boron nitride nanotubes (Won and Aluru [263]), and surfactants such as Newton Black films (Di Napoli and Gamba, [264]).…”
Section: Other Confining Mediamentioning
confidence: 99%
“…Experimental studies have demonstrated heterogeneous water dynamics inside aluminophosphate (AlPO 4 ) NTs, with the water structure controlled mainly by the pore’s surface heterogeneity . In a recent molecular dynamics (MD) study on the anomalous diffusion of water confined in AlPO 4 NTs, we have found that water molecules moved preferentially next to the oxygen sites at the nanotube surface; consequently, helicoidal structures were shown at very low densities with mobility increasing with density. Interestingly, Zang and colleagues have shown different diffusion of water through aluminosilicate (AlSi) NTs in comparison with other hydrogen-bonded liquids (methanol and ethanol), which highlights the peculiarities of water transport through heterogeneous nanopores.…”
Section: Introductionmentioning
confidence: 98%
“…Water confined in the nanopores of hydrophilic AlPO 4 -54· x H 2 O has been the subject of several recent studies involving variable pressure–temperature conditions. AlPO 4 -54· x H 2 O (hexagonal VFI structure, space group P 6 3 , a = 18.9678(13) Å and c = 8.0997(4) Å, Al 18 P 18 O 72 · x H 2 O) exhibits highly hydrophilic one-dimensional (1D) pores along the c direction, with a diameter of 12.7 Å, which are among the largest pores known for zeolites and aluminophosphates. In the pores, H 2 O molecules form a disordered hydrogen-bonded network at ambient temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%